Fading memory of deformation history in carbon black-filled thermoplastic elastomers. (April 2017) - Dusunceli, Necmi; Drozdov, Aleksey D.
Abstract: Observations are reported on a carbon black–reinforced thermoplastic elastomer in multistep uniaxial tensile cyclic tests with a mixed deformation program (oscillations between maximum elongation ratios k max and various minimum stresses σ min with k max monotonically increasing with number of cycles n). Fading memory of deformation history is demonstrated: when specimens are subjected to two loading programs that differ along the first n  −1 cycles of deformation and coincide afterwards, their stress–strain diagrams become identical starting from the n th cycle. A constitutive model is developed in cyclic viscoplasticity with finite deformations, and its adjustable parameters are found by fitting the observations. Ability of the stress–strain relations to describe the fading memory phenomenon and to predict the mechanical response of polymer composites in multi-step cyclic tests with large strains is confirmed by numerical simulation.